2017
DOI: 10.1007/s12098-016-2272-2
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorders — Diagnosis and Management

Abstract: Autism Spectrum Disorder (ASD) is a neuro-developmental disorder commonly seen in children. It is characterized by age inappropriate, impaired social communication and the presence of stereotypic behavior. This disorder is hypothesized to result from cerebral dysfunction arising from a complex interaction between genetic, epigenetic and environmental factors. ASD should be suspected in children failing ASD specific screening tests, in the presence of red flags in social, language and/or play domains, in childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 13 publications
1
46
0
4
Order By: Relevance
“…Stress can increase the risk for depression and anxiety for children with ASD (Green & Ben‐Sasson, ; Simonoff et al, ). Characteristics and symptoms of ASD are not easily changed (Mukherjee, ). However, behavioral interventions have empirical support for helping children with ASD, which can be tailored to the age of the child (LeBlanc & Gillis, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress can increase the risk for depression and anxiety for children with ASD (Green & Ben‐Sasson, ; Simonoff et al, ). Characteristics and symptoms of ASD are not easily changed (Mukherjee, ). However, behavioral interventions have empirical support for helping children with ASD, which can be tailored to the age of the child (LeBlanc & Gillis, ).…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics and symptoms of ASD are not easily changed (Mukherjee, 2017). However, behavioral interventions have empirical support for helping children with ASD, which can be tailored to the age of the child (LeBlanc & Gillis, 2012).…”
Section: Understanding Others' Emotions (Empathy)mentioning
confidence: 99%
“…Estimasi peningkatan 30% selama periode 2012 sampai dengan 2014 menunjukkan insiden anak laki laki dengan GSA 5 kali lebih sering daripada anak perempuan (Ghalichi, Ghaemmaghami, Malek, & Ostadrahimi, 2016). Prevalensi GSA yang meningkat dari 0,04 menjadi 0,50 dalam 30 tahun terakhir disebabkan karena diagnosis ditegakkan pada usia yang lebih muda (Mukherjee, 2017). Peningkatan kasus GSA pada anak berdampak pada peningkatan kepedulian terhadap anak dengan GSA baik dari bidang kesehatan maupun dari masyarakat.…”
Section: Gangguanunclassified
“…In addition to these core features, many other nonspecific behaviors, such as anxiety, depression, sleeping, and eating disorders, are quite common. It has been found that features of ASD are often accompanied by impairments in cognitive and adaptive functioning, learning styles, and attention skills [3,4].…”
Section: Introductionmentioning
confidence: 99%